2017
DOI: 10.1016/j.ijadhadh.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behavior of adhesive anchors under high temperature exposure: Experimental investigation

Abstract: The improvement in mechanical and adhesion properties of polymer resins have allowed to progressively substitute cast-in place rebars by polymer-based anchors in some applications, by providing equivalent or even higher mechanical properties at ambient temperature. However, a temperature increase has the effect of weakening the bond and leads to a significant decay in the bearing capacity of the adhesive anchors. This paper presents a study of the phenomena that occur at high temperature in an adhesive anchor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 20 publications
4
26
0
1
Order By: Relevance
“…Indeed, temperature seems to be the factor that affects the most the mechanical behavior of chemical PIRs. In a previous paper [23], we showed that the temperature increase up to values blow the resin glass transition temperature leads to increase the mechanical properties of chemical PIRs due to the resin post-cure phenomenon. However, when temperature exceeds the resin glass transition temperature, a change in viscosity and physical state occur [24], leading therefore to a new bond stress distribution along the bond joint [25] [26].…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…Indeed, temperature seems to be the factor that affects the most the mechanical behavior of chemical PIRs. In a previous paper [23], we showed that the temperature increase up to values blow the resin glass transition temperature leads to increase the mechanical properties of chemical PIRs due to the resin post-cure phenomenon. However, when temperature exceeds the resin glass transition temperature, a change in viscosity and physical state occur [24], leading therefore to a new bond stress distribution along the bond joint [25] [26].…”
Section: Introductionmentioning
confidence: 88%
“…The relationship between the bond strength and temperature is obtained experimentally through pullout tests performed by applying a constant bond stress in the adhesive joint. The description of the test procedure and the main results are presented in a previous paper [23]. The tests are performed on steel rebars bonded into concrete cylinders (160 mm diameter and 250 mm height) using the same epoxy resin than that will be used in the full-scale fire test.…”
Section: Bond Strength -Temperature Relationship ( (θ))mentioning
confidence: 99%
See 3 more Smart Citations